Risk of new onset hyperuricemia and chronic kidney disease after living kidney donation through propensity score matching analysis - Kao, Yu-Nong; Huang, Shih-Ting; Wang, I-Kuan; Chuang, Ya-Wen; Lin, Cheng-Li; Lee, Brian K.; Li, Chi-Yuan; Yu, Tung-Min (Scientific reports, 2024)
Living kidney donors have been regarded as those people having earned the healthiest status level after having undergone scrutiny. Although one’s post-donation GFR is expected to fall to 50% of their pre-donation value, it is well documented that there is a compensatory increase in GFR which subsequently reaches approximately 60–70% of the donor’s pre-donation value. Data regarding gout/hyperuricemia in living kidney donors has remained scarce until now. This study involved kidney donors enrolled within the years 2000 to 2017, where those who were selected to be matched to those in group of case cohort by age, year of index date, gender and co-morbidity were considered as the control cohort. During the 17-year study period 2,716 participants were enrolled. Results revealed that kidney donors experienced a risk of new onset gout/ hyperuricemia (adjusted HR = 1.73; 95%CI = 1.27, 2.36), and new onset CKD (adjusted HR = 6.7; 95% CI = 4.4, 10.21) were found to be higher in kidney donors. Our findings suggest that people after kidney donation are significantly associated with a higher risk of new onset gout/hyperuricemia. Clinical professionals therefore need to be cautious of new onset gouy/hyperuricemia after donation surgery.